Perbedaan Strategi Manajemen Modal Kerja pada Bank BCA dan Bank Mandiri di Indonesia - Nadya Aura Wulan Savitri; Masrifatul Roidha; Rindyi Putri Lestari; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Working capital management is an important aspect in banking to maintain smooth operations and financial stability. This research aims to analyze the differences in working capital management strategies at Bank BCA and Bank Mandiri, the two largest banks in Indonesia. The research method used is comparative descriptive using secondary data in the form of the annual financial reports of both banks for the 2019-2023 period. The results showed that Bank BCA has a more effective working capital management strategy than Bank Mandiri. BCA Bank has healthy financial ratios and shows good performance. Meanwhile, Bank Mandiri has quite stable financial ratios. Even though Bank Mandiri's NPL is relatively high, this bank has quite high ROA, ROE and CAR.